PROFIL PENGGUNA VAPE DI KOTA PEKANBARU (STUDI KASUS GAYA HIDUP MAHASISWA DI KELURAHAN SIMPANG BARU) - Arif Rahman Hakim; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in the area of Simpang Baru village. The purpose of this study was to analyze the process of college students getting to know Vape in Simpang Baru Village and how the socio-economic background of college students in Simpang Baru Village. The writer used qualitative descriptive methods and the instruments of the data were observation, interviews, and documentation. The average that college students were knew vape from cyberscape and peers. Before consuming the vape, many of college students were also the active smokers. They have been start smoking in the early age until becoming active smokers. All informants were not from pekanbaru city, but they come from different areas. Most of informants ranted boarding houses and some were living with their relatives. The informants got money from their parents, but some of them already working. On average, the informants came from the capable families. It has been seen from their parents' work. Some of them work as civil servants, enterpreneurs, and some work as farmers. Most of informants' parent didn't know that their children were consumed vape, but some of them knew that their children were consumed it.Keyword: profile, vape, and the college students in Simpang Baru.